Minutes of General Council (extract)
015b_0021_001 G.C. MINUTES 23RD DECEMBER, 1936. GENERAL COUNCIL OF THE I.F.T.U. AND L.S.I. BUREAU. Under this item, Report of meeting of the General Council of the International Federation of Trade Unions and Labour and Socialist International Bureau, held on the 4th and 5th December, 1936, in Paris, was considered. Sir Walter Citrine supplemented the Report and referred to Mr. Grenfell's report on his visit to Spain. On the motion of Mr. Hicks, the Report was ADOPTED. It was understood that a statement on the help given to the Spanish Trade Unionists and Socialists be circulated to every branch of the affiliated Trade Unions 292/946/15b/21